Pengaruh Kesadaran Kesehatan Dan Pengetahuan Produk Terhadap Minat Beli Pada Produk Menstrual PAD : Studi Pada Tenaga Kerja Kesehatan Perempuan Di Puskesmas Pomalaa - Nurul Khairunnisa Ar-Rahmah; Almansyah Rundu Wonua; Ismanto Ismanto (PPIMAN Pusat Publikasi Ilmu Manajemen, 2023)
This study aims to determine: (1) The Effect of Health Awareness on Buying Interest in Menstrual Pad Products (Study on female health workers at the Pomalaa Health Center). (2) The Effect of Product Knowledge on Buying Interest in Menstrual Pad Products (Study on female health workers at the Pomalaa Health Center). This research uses a quantitative method approach. Data collection in this study used observation and questionnaires. The population of this study were all female health workers at the Pomalaa Health Center. While the sample of this study amounted to 62 female health workers by determining the sample using purposive sampling technique. Testing of research instruments using validity test and reliability test with SPSS 25.0. The data analysis technique used in this research is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through measurement model testing (outer model) and structural model testing (inner model) with Smart PLS 4.0. Based on the results of the study, it is known that the Health Awareness variable has a positive and significant effect on Purchase Intention as indicated by the P-Values value of 0.000. And the Product Knowledge variable also has a positive and significant effect on Purchase Intention, this is indicated by the P-Values value of 0.000.